Античкиот идеал на καλοκἀγαθία низ призмата на епиграфските сведоштва - Џукеска, Елена (Филозофски факултет, Скопје, 2016)
The expressions καλοκἀγαθία and καλὸς καὶ ἀγαθός (καλὸς κἀγαθός) are recorded not only in the Ancient Greek literature, but also on epigraphic monuments. On the honorific decrees from the Hellenistic ‒ Roman period the phrase ἀρετᾶς ἕνεκεν καὶ εὐνοίας καὶ εὐεργεσίας, "on account of the excellence, goodwill and benefaction", typically stated as a formal reason for conferring an honor to a citizen, is often substituted by the phrase ἀρετῆς ἕνεκεν καὶ εὐνοίας καὶ καλοκἀγαθίας, meaning "on the account of the excellence, goodwill and nobleness". In other variations of this phrase and in different contexts, καλοκἀγαθία is coupled with εὐσέβεια, "reverence", δικαιοσύνη, "righteousness", φιλοστοργία, "affectionateness", πρόνοια, "forethought" and other nouns denoting internal qualities of a person. Although the epigraphic evidence is not archaic it reveals important aspects which are relevant for the understanding of the ancient ideal of καλοκἀγαθία. The comparison of the examples found on inscriptions and in literary works shows that the meaning of καλοκἀγαθία on the inscriptions from the Hellenistic ‒ Roman period is very often confined to εὐεργεσία, "well-doing, benefaction" and that the description of the person who is καλὸς κἀγαθός no longer includes adjectives relative to the physical beauty.
The Ancient Ideal of καλοκἀγαθία through the Prism of Epigraphic Evidence
Keywords: καλοκἀγαθία, καλὸς καὶ ἀγαθός, epigraphic monuments